Metabolic peculiarities in laboratory rats during biodegradation of an implant made of a magnesium-based alloy - Golovakha, Maksim; Belyenichev, Igor; Chorny, Vadim; Yatsun, Yevgeniy (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
The article contains information on the study of possible toxic effects of products of biodegradation of an original magnesium-based alloy on laboratory rats. Laboratory methods of examination are described. Plasma biochemical parameters, which were used for assessing the endogenous intoxication in rats, are characterized. It was found out that biological resorption products of the alloy did not cause any toxic effects on tissues of the organism and did not increase cell destruction, as it was evidenced by absence of signs of endogenous intoxication and oxidative damage of functional macromolecules.